Some Valid Generalizations of Boyd and Wong Inequality and ψ,ϕ-Weak Contraction in Partially Ordered b−Metric Spaces - Noor Jamal; Thabet Abdeljawad; Muhammad Sarwar; Nabil Mlaiki; Panda Sumati Kumari (International Journal of Mathematics and Mathematical Sciences)
In this manuscript, we use ψ,ϕ-weak contraction to generalize coincidence point results which are established in the context of partially ordered b-metric spaces. The presented work explicitly generalized some recent results from the existing literature. Examples are also provided to show the authenticity of the established work.